Entrance and Growth of Lactic Acid Bacteria in Gas-Exchanged, Brined Cucumbers - Daeschel, M. A. (1981)
Entrance of lactic acid bacteria into the interior of brined cucumbers was found to be greatly influenced by gas composition of the cucumbers before brining. Exchange of the internal gas of fresh cucumbers with O(2) resulted in absorption of bacteria into the subsequently brined fruit within a few hours. Bacteria were absorbed into nonexchanged cucumbers to a lesser extent. Little bacterial absorption occurred in N(2)-exchanged cucumbers. Stomata of the cucumber skin appeared to be a likely port for bacterial entry. When Pediococcus cerevisiae or Lactobacillus plantarum cells were added to the brine of O(2)-exchanged cucumbers, the respective cell types colonized in large numbers within intercellular spaces and vascular elements of mesocarp tissue during fermentation of the cucumbers. Implications of these observations, particularly with regard to bloater formation in brined cucumbers, are discussed.